PENGARUH PERKEMBANGAN TEKNOLOGI TERHADAP MINAT KONSUMEN MENGGUNAKAN JASA PENGIRIMAN EKSPRESS DI PT. POS INDONESIA KOTA KENDARI - Nursaadha Rajuddin, Wa Ode; Azis Muthalib, Dzulfikri; Naim, Ifin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
This study aims to determine and examine the effect of technological developments on consumer interest in using Express Delivery Services at PT. Kendari City Post Indonesia. The population in this study is that this research will be limited by using the following criteria: (1) Consumers who make transactions at Express Delivery Services at PT. Pos Indonesia Kendari City, (2) Has been a consumer for more than 1 year. Sampling was carried out Sampling was carried out at PT. Pos Indonesia, Kendari City, with a total sample in this study of 60 respondents. Collecting data in this study is to use a questionnaire and documentation. Methods of Analysis Descriptive Statistical Analysis and Simple Linear Regression Analysis. The results of this study are: namely: technological developments have a positive and significant effect on consumer interest in using Express Delivery Services at PT. Pos Indonesia Kendari City